Effect of the Initial Temperature of Extraction of Neem Cake (Azadirachta indica A. JUSS) on its Toxicity on Crocidolomia pavonana (F.) Larvae - Fhera Hardiani; Danar Dono; Ceppy Nasahi (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2019)
Crocidolomia pavonana is an important pest that attacks the Brassicaceae. Neem cake is waste from neem seed pressing that can be used as a botanicals insecticide to control insect pests. The effect of the initial temperature of extraction can have an impact on the toxicity of the extract. The aim of this study was to determine the best initial temperature for the extraction of neem cake on mortality, larval development time, feed consumption, larval weight and survival of larvae into pupae and adult. The experimental method used in this research was Randomized Completely Design (RCD) with 4 treatments and 4 replication, i.e. control, extraction of neem cake at initial temperature of 30°C, initial temperature 50°C, and initial temperature 70°C which allows two concentrations of 1% and 3%. The results of the research with the best toxicity were shown in the initial extraction temperature of 50°C at concentrations of 1% and 3% with the mortality reaching 82.5% and 90%. The initial temperature extraction of 50°C also showed lengthened of the larval development time, decreased feeding activity, larval weight and survival of larvae to develop into pupae and imago.